The Role of People's Representatives Council and President Post the Amendment to Basis of the 1945 Law in The Establishment of Law - Pradijonrika, Heru (Riviera Publishing, 2022)
Introduction: The powers of the President according to the 1945 Constitution of the Republic of Indonesia include administrative, legislative, judicial, military, and diplomatic powers. After four amendments to the 1945 Constitution of the Republic of Indonesia, the power of the President was significantly reduced. Many people think that there has been a shift in power towards strengthening parliamentary institutions (legislative heavy). Method: This research is a type of normative research, data collection techniques through literature study methods. Result: The first amendment to the 1945 Constitution of the Republic of Indonesia in the 1999 MPR General Session contained several articles to avoid the accumulation of President's power, thus opening opportunities for the realization of the concept of power sharing. The shift or handover of legislative power from the President to the House of Representatives due to the First Amendment of the 1945 Constitution (Article 5 paragraph 1 and Article 20 paragraph 1), at least several things should be considered: first, the shift in legislative power from the President to the DPR means strengthening the position and function of the people's representatives council (DPR) as an institution legislative. Conclusion: Post-Amendment to the 1945 Constitution resulted in a new format for the House of Representatives, in which the role and authority of the House of Representatives became stronger than the President. With this shift, the President is not in full power when forming the Law.